2017
DOI: 10.17126/joralres.2017.038
|View full text |Cite
|
Sign up to set email alerts
|

Tongue lesions and anomalies in a sample of Yemeni dental patients: A cross-sectional study.

Abstract: Background: Tongue examination helps considerably in diagnosing the un derlying health state of the patient, especially in the cases of chronic diseases. The aim of this study is to determine the prevalence and association of tongue lesions with risk factors among Yemeni dental patients. Materials and methods: An oral medicine specialist examined all 713 patients attending the dental polyclinics at the University of Sciences and Technology (Sana'a, Yemen). The examination sheet was designed to include informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
3
9
2
Order By: Relevance
“…The mean age of the patients in the present study was 45.26 years which is in accordance with most previous studies based on histopathological examination; 44.50 years by Miyake et al, 28 45.30 years by Costa et al, 26 46.41 years by Lasisi and Abimbola, 25 47.00 years by Alaeddini et al, 2 48.00 years by Shamloo et al, 24 but higher than 24.00 years by Al-Wesabi et al, 16 33.00 years by Byahatti and Ingafou, 19 36.51 years by Mushatat et al, 21 or in the 6 to 10-year-aged group by Vörös-Balog et al 18 The study by Vörös-Balog et al 18 focused on tongue lesions in Hungarian children. The studies by Al-Wesabi et al 16 and by Byahatti and Ingafou 19 used median age instead of mean age.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The mean age of the patients in the present study was 45.26 years which is in accordance with most previous studies based on histopathological examination; 44.50 years by Miyake et al, 28 45.30 years by Costa et al, 26 46.41 years by Lasisi and Abimbola, 25 47.00 years by Alaeddini et al, 2 48.00 years by Shamloo et al, 24 but higher than 24.00 years by Al-Wesabi et al, 16 33.00 years by Byahatti and Ingafou, 19 36.51 years by Mushatat et al, 21 or in the 6 to 10-year-aged group by Vörös-Balog et al 18 The study by Vörös-Balog et al 18 focused on tongue lesions in Hungarian children. The studies by Al-Wesabi et al 16 and by Byahatti and Ingafou 19 used median age instead of mean age.…”
Section: Discussionsupporting
confidence: 91%
“…For example, mucus extravasation phenomenon (mucocele) preferentially occurred at the ventral surface of the tongue, squamous cell carcinoma and epithelial dysplasia at the lateral border of the tongue, and lichen planus/lichenoid reaction at lateral border of the tongue followed by dorsal surface of the tongue, respectively. Most of the clinical studies 5,[16][17][18][19][20][21] revealed that fissured tongue was the most common tongue lesion. However, the study by Avcu and Kanli 14 found that coated tongue was the most prevalent tongue lesion followed by fissured tongue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The male and female ratio is 1.34:1. Mohammed Ali Al-Wesabi et al 7 shows incidence in male 51.6% and female 48.4% which is almost similar to our observation.…”
Section: Discussionsupporting
confidence: 91%